The Early Cretaceous Tsagaangol formation sandstone provenance and paleoclimate - Nansalmaa, Dashpuntsag; Jargal, Luvsanchultem; Batbold, Demberelsuren; Enkhtuya, Altangadas; Bolormaa, Enkhbayar (Geological Issues, 2023)
Early Cretaceous Tsagaangol formation refers to Zoolen terrain. This study attempts to make classification of the sandstones of the formation, define its sources and identify its alteration and paleoclimate condition. The sandstones of the formation are rich in mineral fragments, especially, quartz (comprising 70-75% of the entire content) and the composition is identified to be varying from subarcose to lithic arcose. As plotted on the source defining diagrams, they have been identified to be of continental block and mixed orogen and to get intensely altered or weathered under warm humid climate condition.